Political Reservation and Female Labor Force Participation in Rural India - Deininger, Klaus (World Bank, Washington, DC, 2020)
Despite income growth, fertility decline, and educational expansion, women's labor force participation in rural India dropped precipitously over the last decade. This paper uses nationwide, individual-level data allow to explore whether random reservation of village leadership for women affected their access to suitable job opportunities, demand for participation in the labor force, and income as well as intrahousehold bargaining in the short and medium term. Political empowerment through reservation affected women's but not men's participation in public works, but also women's participation in labor markets, income, and participation in key household decisions, with a lag.